Developing the course “Ecology and Ecosystems Science in Relation to Environmental Economics” - Stupak, Inge; Vesterdal, Lars; Ingerslev, Morten (Improving University Science Teaching and Learning, 2023)
This work reports group work by three colleagues involved in the establishment of a new MSc level course in natural resource ecology. The report therefore reflects our current effort to design and establish a new course and at the same time serves to meet the requirements for passing the course in university pedagogy.